2009
DOI: 10.1590/s0037-86822009000300016
|View full text |Cite
|
Sign up to set email alerts
|

Lagochilascaris minor: antibody production in experimentally infected mice

Abstract: Lagochilascaris minor is the causative agent of lagochilascariosis, a disease that affects the neck region and causes festering abscesses, with eggs, adult parasites and L3/L4 larvae within the purulent exudates. Today, mice are considered to be intermediate hosts for the parasite. C57BL/6 mice produce immunoglobulin IgM, IgA and IgG against the crude extract of the parasite; on the other hand, antibodies produced against the secreted/excreted antigens of Lagochilascaris minor present lower levels of IgM, IgA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…IL-6, a multifunctional cytokine, is involved in the regulation of inflammatory responses [31]. Studies have shown that IL-6 expression is critical during the acute phase of helminth infections in mice, enhancing IgA secretion in the gastrointestinal mucosa and inducing fever during inflammation [32][33][34]. The response may play a crucial role in the immunological interaction between H. contortus and its host.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, a multifunctional cytokine, is involved in the regulation of inflammatory responses [31]. Studies have shown that IL-6 expression is critical during the acute phase of helminth infections in mice, enhancing IgA secretion in the gastrointestinal mucosa and inducing fever during inflammation [32][33][34]. The response may play a crucial role in the immunological interaction between H. contortus and its host.…”
Section: Discussionmentioning
confidence: 99%
“…Lagochilascaris minor is the most important, since it is the only species causing human lagochilascariasis. 5 Animal experiments have provided insight into the life cycle of this helminth. Probably mice and other rodents are intermediate hosts for the parasite and can be infected by ingestion of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…During experimental infection with Heligmosomoides polygyrus , antibodies block the intestinal invasion in the earliest days of the infection [ 34 ]. BALB/c mice have been demonstrated to produce IgM, IgG, IgA, and IgE against the parasite's crude extract (CE) and secreted-excreted (SE) antigens, with a higher production of IgA, IgM, and IgG in response to the CE antigens than to the SE products of L. minor [ 11 ]. These results suggest that the large number of CD19+ cells in the spleens of BALB/c mice is associated with the increased production of antibodies that participate in the resistance to L. minor infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the difference in the susceptibility of mice to experimental lagochilascariosis can be influenced by the individual immune response, which plays an essential role in the progression of the infection by reducing or blocking the pathological processes [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation